2009
DOI: 10.1590/s0100-29452009000200020
|View full text |Cite
|
Sign up to set email alerts
|

Fruit quality of 'Tahiti' lime (Citrus latifolia Tanak) grafted on twelve different rootstocks

Abstract: In the present work, the effect of twelve rootstocks on fruit quality of the nucellar clone IAC-5 of 'Tahiti' lime, (Citrus latifolia Tanaka) and the influence of fruit position on tree in fruit quality was evaluated in the Citrus Experimental Station of Bebedouro (EECB), located in the Bebedouro county, state of São Paulo, Brazil. A 8.0 x 5.0m planting frame was utilized. The evaluated rootstocks were: 'Carrizo' citrange (C. sinensis (L.) Osbeck x Poncirus trifoliata (L.) Raf.); the hybrids 'Rangpur' lime x '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
2
15

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 4 publications
3
2
2
15
Order By: Relevance
“…the averages found were higher than those obtained by Stenzel and Neves (2004), who reported values between 5.0 and 5.8%, whereas in the present study, titratable acidity ranged from 6.00 to 7.52%, considering the three evaluations. these acidity levels are similar to those described by Stuchi et al (2009) from 6 to 8%, which according to the authors, are close to the commercial standards demanded by the market, which is 7-8%.…”
Section: 'Limeira' Trifoliate (496) (Table 2)supporting
confidence: 89%
See 1 more Smart Citation
“…the averages found were higher than those obtained by Stenzel and Neves (2004), who reported values between 5.0 and 5.8%, whereas in the present study, titratable acidity ranged from 6.00 to 7.52%, considering the three evaluations. these acidity levels are similar to those described by Stuchi et al (2009) from 6 to 8%, which according to the authors, are close to the commercial standards demanded by the market, which is 7-8%.…”
Section: 'Limeira' Trifoliate (496) (Table 2)supporting
confidence: 89%
“…In this evaluation, 'Cleopatra' mandarin rootstock induced the highest value (82.12 g), but this trend was not confirmed in evaluations in the following years (taBle 2). the fresh fruit mass values were lower than those reported by Stuchi et al (2009), who obtained average values of 91 g, while in the present study, the mass values ranged from 71.17 to 82.12 g. Table 2 shows significant differences among treatments in relation to the number of fruits per plant in all evaluation years. there is also an increase in the production of fruits per plant over the years.…”
Section: Resultscontrasting
confidence: 74%
“…Regarding fruit dimensions, the data presented in this study were superior to those reported by Figueiredo et al, (2002) for 'IAC-5' and similar to those reported by Stuchi et al, (2009) for 'IAC-5.1'. In Bebedouro, São Paulo, fruits with 'IAC-5' canopy over many rootstocks did not differ in terms of mass, length and fruit diameter (Figueiredo et al, 2002).…”
Section: Fruit Qualitysupporting
confidence: 68%
“…In Bebedouro, São Paulo, fruits with 'IAC-5' canopy over many rootstocks did not differ in terms of mass, length and fruit diameter (Figueiredo et al, 2002). In contrast, 'IAC-5.1' fruits in combination with eleven rootstocks presented differenc- es for the following attributes: soluble solids, ratio, peel thickness, percentage of juice and fruit mass (Stuchi et al, 2009).…”
Section: Fruit Qualitymentioning
confidence: 85%
“…All rootstocks produced fruit with desirable color for export (Table 4), with CI > 2.0 (Spósito et al, 2006), and there was no effect of rootstock on this trait. This is in agreement with Stuchi et al (2009), who found no differences in fruit coloration of Tahiti limes grafted onto different rootstocks. There was a high incidence of Alternaria brown spot on fruits of Lee.…”
Section: Resultssupporting
confidence: 93%